Development of Ganoderma lucidum spore powder based proteoglycan and its application in hyperglycemic, antitumor and antioxidant function. (September 2019) - Zhu, Li-Fang; Yao, Yuanfa; Ahmad, Zeeshan; Chang, Ming-Wei
Graphical abstract: Highlights: Proteoglycan from GLSP (ganoderma lucidum spore powder) was optimized via RSM. Effect of cracked and uncracked GLSP on the amino acids content was significant. Cracked or uncracked GLSP effects extraction of amino acid and polysaccharide. Proteoglycans show antioxidant and hypoglycemic activity. Proteoglycans show antitumor and antibacterial activity. Abstract: A new natural proteoglycan from Ganoderma lucidum spore powder (GLSP) was obtained via solvent extraction and optimized using response surface methodology (RSM). The differences among the characteristics of the new proteoglycan from cracked (proteoglycan-C) and uncracked GLSP (proteoglycan-UC) were explored. The SDS-PAGE results showed the molecular weight of protein contained in proteoglycan-UC (55, 72, 95 kDa) was different to that proteoglycan-C (43, 95 kDa). The differences of these amino acids (Glu, Arg, Leu and Lys) content and monosaccharides (Fuc, Gal, Glc, Man and Gal-AC) content between proteoglycan-C and proteoglycan-UC were determined by HPLC/ ion chromatography. The 2, 2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities of proteoglycan-C were higher than that proteoglycan-UC. The proteoglycan-UC exhibited stronger hypoglycemic and antibacterial effects against E. coli and S. aureus, and the proteoglycan-C and proteoglycan-UC showed antitumor effects with potential for therapeutic applications.